2014
DOI: 10.1159/000369776
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic Strokes with Reversible Vasoconstriction and without Thunderclap Headache: A Variant of the Reversible Cerebral Vasoconstriction Syndrome?

Abstract: Background: Reversible vasoconstriction (RV) may cause ischaemic stroke (IS) in the absence of any other defined stroke aetiology. The three objectives of our study were to evaluate the frequency of RV in a prospective series of young IS patients, to describe the detailed clinical-radiological features in the patients with RV and IS, and to compare these characteristics with those of reversible cerebral vasoconstriction syndrome (RCVS). Methods: We identified between October 2005 and December 2010, 159 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 28 publications
1
58
2
3
Order By: Relevance
“…Similarly to headache patterns, these figures vary according to inclusion criteria and mode of recruitment into the studies. The frequency of RCVS as a cause for IS has been evaluated in a few studies …”
Section: Methodsmentioning
confidence: 99%
“…Similarly to headache patterns, these figures vary according to inclusion criteria and mode of recruitment into the studies. The frequency of RCVS as a cause for IS has been evaluated in a few studies …”
Section: Methodsmentioning
confidence: 99%
“…However, currently there is a dearth of epidemiological data supporting an association between cannabis use and stroke. 8,9 Thus, our current knowledge about cannabis-associated strokes is based almost exclusively on clinical reports. 10 Although there have been a few general population studies, these have been mostly based on hospital records and are, therefore, retrospective in nature.…”
mentioning
confidence: 99%
“…The TCD taken two days after onset also showed increased flow velocity at left MCA, which was normalized in the follow-up study. The vasoconstriction in RCVS was typically described as bilateral, but Submit your Manuscript | www.austinpublishinggroup.com unilateral RCVS is also well recognized in previous literatures [8]. RCVS can be caused by various medical conditions including alcohol and can also occur spontaneously [2][3][4].…”
Section: Discussionmentioning
confidence: 92%
“…The patient in this case might have headache, but we could not identify it due to his aphasia. Furthermore, previous literatures showed that about 15% of RCVS patients expressed non-thunderclap or no headache [8,9]. Cardioembolism and intracranial atherosclerosis were excluded by negative findings in appropriate evaluations.…”
Section: Discussionmentioning
confidence: 99%